A family of PIKFYVE inhibitors with therapeutic potential against autophagy-dependent cancer cells disrupt multiple events in lysosome homeostasis. Issue 10 (3rd October 2019) - Sharma, Gaurav; Guardia, Carlos M.; Roy, Ajit; Vassilev, Alex; Saric, Amra; Griner, Lori N.; Marugan, Juan; Ferrer, Marc; Bonifacino, Juan S.; DePamphilis, Melvin L.
ABSTRACT: High-throughput screening identified 5 chemical analogs (termed the WX8-family) that disrupted 3 events in lysosome homeostasis: (1) lysosome fission via tubulation without preventing homotypic lysosome fusion; (2) trafficking of molecules into lysosomes without altering lysosomal acidity, and (3) heterotypic fusion between lysosomes and autophagosomes. Remarkably, these compounds did not prevent homotypic fusion between lysosomes, despite the fact that homotypic fusion required some of the same machinery essential for heterotypic fusion. These effects varied 400-fold among WX8-family members, were time and concentration dependent, reversible, and resulted primarily from their ability to bind specifically to the PIKFYVE phosphoinositide kinase. The ability of the WX8-family to prevent lysosomes from participating in macroautophagy/autophagy suggested they have therapeutic potential in treating autophagy-dependent diseases. In fact, the most potent family member (WX8) was 100-times more lethal to 'autophagy-addicted' melanoma A375 cells than the lysosomal inhibitors hydroxychloroquine and chloroquine. In contrast, cells that were insensitive to hydroxychloroquine and chloroquine were also insensitive to WX8. Therefore, the WX8-family of PIKFYVE inhibitors provides a basis for developing drugs that could selectively kill autophagy-dependent cancer cells, as well as increasing the effectiveness of established anti-cancer therapies through combinatorial treatments. Abbreviations: ACTB: actin beta; Baf: bafilomycin A1 ; BECN1: beclin 1; BODIPY: boron-dipyrromethene; BORC: BLOC-1 related complex; BRAF: B-Raf proto-oncogene, serine/threonine kinase; BSA: bovine serum albumin; CTSD: cathepsin D; CQ: chloroquine; DNA: deoxyribonucleic acid; EC50 : half maximal effective concentration; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFP: green fluorescent protein; HCQ: hydroxychloroquine; HOPS complex: homotypic fusion and protein sorting complex; Kd: equilibrium binding constant; IC50: half maximal inhibitory concentration; KO: knockout; LAMP1: lysosomal associated membrane protein 1; MAP1LC3A: microtubule associated protein 1 light chain 3 alpha; MES: 2-(N-morpholino)ethanesulphonic acid; MTOR: mechanistic target of rapamycin kinase; μM: micromolar; NDF: 3-methylbenzaldehyde (2, 6-dimorpholin-4-ylpyrimidin-4-yl)hydrazine;NEM: N-ethylmaleimide; NSF: N-ethylmaleimide sensitive factor; PBS: phosphate-buffered saline; PIKFYVE: phosphoinositide kinase, FYVE-type zinc finger containing; PIP4K2C: phosphatidylinositol-5-phosphate 4-kinase type 2 gamma; PtdIns3P: phosphatidylinositol 3-phosphate; PtdIns(3, 5)P2 : phosphatidylinositol 3, 5-biphosphate; RFP: red fluorescent protein; RPS6: ribosomal protein S6; RPS6KB1: ribosomal protein S6 kinase B1; SQSTM1: sequestosome 1; TWEEN 20: polysorbate 20; V-ATPase: vacuolar-type H + -translocating ATPase; VPS39: VPS39 subunit of HOPS complex; VPS41: VPS41 subunit of HOPS complex; WWL: benzaldehyde [2, 6-di(4-morpholinyl)-4-pyrimidinyl]hydrazone; WX8: 1H-indole-3-carbaldehyde [4-anilino-6-(4-morpholinyl)-1, 3, 5-triazin-2-yl]hydrazine; XBA: N-(3-chloro-4-fluorophenyl)-4, 6-dimorpholino-1, 3, 5-triazin-2-amine hydrochloride; XB6: N-(4-ethylphenyl)-4, 6-dimorpholino-1, 3, 5-triazin-2-amine hydrochloride